Fabrication of Amphotericin-B-loaded Sodium Alginate Nanoparticles for Biomedical Applications - ULAĞ, SONGÜL; ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (My University, 2022)
In this study, amphotericin-B (AMB)-loaded sodium alginate (SA) nanoparticles were fabricated using the electrospraying technique for biomedical applications. AMB is an antifungal agent and is poorly absorbed from the gastrointestinal tract due to its low aqueous solubility. Therefore, it should be given parenterally to treat systemic fungal infections. This study aims to transport it with nanoparticle formulations and observe the nanoparticle release behaviours. Scanning electron microscopy (SEM) images showed that nanoparticles of 0.5% SA fabricated at 37 kV had the most suitable particle diameter (93.36±24.386 nm) for loading 0.5, 1, and 3 ml of AMB. Fourier transform infrared spectroscopy (FTIR) results demonstrated that AMB successfully loaded into 0.5% SA nanoparticles. Drug release behaviours of the AMB-loaded particles indicated that AMB was released with a burst at the beginning, and release behaviour became sustainable after half an hour. The encapsulation efciencies of the diferent amounts of drug were calculated, and the results showed that the highest encapsulation efciency belonged to the 0.5% SA/1 AMB nanoparticles (42±1.23%).
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, BİYOMATERYAL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Biyomalzemeler; Malzeme Bilimi (çeşitli); Genel Malzeme Bilimi; Fizik Bilimleri; Biomaterials; Materials Science (miscellaneous); General Materials Science; Physical Sciences; Amphotericin-B; Biomedical; Drug release; Electrospraying; Nanoparticle; Sodium alginate